KEBIJAKAN PEMBIAYAAN PERGURUAN TINGGI NEGERI DI INDONESIA : ANALISIS SKEMA BLU DAN PTNBH - Siti Rahmatullisa; Saipul An-Nur; Ade Rosad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The financing policy for state universities in Indonesia has undergone a strategic transformation through the implementation of the Public Service Agency (BLU) and the Legal Entity State Universities (PTNBH) schemes. Both models are designed to provide financial flexibility, enhance institutional independence, and strengthen the effectiveness of higher education services. This study aims to analyze the differences in the concepts, implementation, and implications of BLU and PTNBH policies on the financing and performance of state universities in the contemporary era. A qualitative approach through literature review was used to obtain a comprehensive overview of various recent research findings. The study results indicate that BLU provides flexibility in managing Non-Tax State Revenue (PNBP), but its budget allocation is often not optimal to support the overall performance of the institution. Meanwhile, PTNBH provides broader autonomy that has the potential to increase financial independence, but also faces challenges in accountability and equitable access to education. This study provides recommendations for strengthening financial governance to ensure the effectiveness of these two financing models.